2023
DOI: 10.3390/foods12183414
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and Microbiome Analysis to Study the Flavor of Summer Black Tea Improved by Stuck Fermentation

Lianghua Wen,
Lingli Sun,
Ruohong Chen
et al.

Abstract: Tea is the most popular and widely consumed beverage worldwide, especially black tea. Summer tea has a bitter and astringent taste and low aroma compared to spring tea due to the higher content of polyphenols and lower content of amino acids. Microbial fermentation is routinely used to improve the flavor of various foods. This study analyzed the relationship between the quality of black tea, metabolic characteristics, and microbial communities after microbial stuck fermentation in summer black tea. Stuck ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Catechins, known for their bitter and astringent properties, impacted the final quality and taste of the tea [18,19]. The high contents of polyphenols and catechins in the Taishan black teas imparted characteristics of heavy and strong and heavy and mellow tastes, consistent with an earlier study [20]. By comparison, it was found that the average proportion of catechins in Taishan black tea was 8.16%, which was much higher than that of Anhui and Yunnan black tea, and the caffeine content of Taishan black tea was 2.3%, which was slightly higher than that of Anhui and Yunnan black tea [21].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Catechins, known for their bitter and astringent properties, impacted the final quality and taste of the tea [18,19]. The high contents of polyphenols and catechins in the Taishan black teas imparted characteristics of heavy and strong and heavy and mellow tastes, consistent with an earlier study [20]. By comparison, it was found that the average proportion of catechins in Taishan black tea was 8.16%, which was much higher than that of Anhui and Yunnan black tea, and the caffeine content of Taishan black tea was 2.3%, which was slightly higher than that of Anhui and Yunnan black tea [21].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the color of the bottom of the leaves revealed that partially brewed Taishan black tea leaves retained a greenish hue, suggesting incomplete fermentation of the fresh tea leaves. The low content of thearubigins in the incompletely fermented black tea leaves resulted in a light and astringent tea soup [20]. This issue was further corroborated by the content of water extracts (Table 2) and the aroma description (Table S1).…”
Section: Discussionmentioning
confidence: 66%
“…The fresh tea was obtained from the Tea Research Institute of Guangdong Academy of Agricultural Sciences (Yingde, Guangdong Province, China). Following traditional processes, fresh tea was processed into BT [13]. The BT is then evenly sprayed with water to preserve its moisture level at 30-35%, stacked for 35 days to allow for natural microbial fermentation, and finally dried, which is processed into EFT [13].…”
Section: Preparation Of Tea Extractsmentioning
confidence: 99%
“…Following traditional processes, fresh tea was processed into BT [13]. The BT is then evenly sprayed with water to preserve its moisture level at 30-35%, stacked for 35 days to allow for natural microbial fermentation, and finally dried, which is processed into EFT [13]. The BT and EFT extracts were referred to the previous methods [23].…”
Section: Preparation Of Tea Extractsmentioning
confidence: 99%
See 1 more Smart Citation